A Fuzzy Based Goal Programming Methodology for Minimizing the Risk Factors: A Real Case Application in Pharmaceutical Sector - Ozkan, Betul; Kaya, Ihsan; Basligil, Huseyin (OLD CITY PUBLISHING INC, 2017)
Pharmaceuticals have been widely used for treating the illnesses and for protecting humans from the diseases for ages. Pharmaceutical supply chain network faces different risks at every stage of the chain. While the end user of a pharmaceutical supply chain is patients, it becomes more important to manage and minimize the risks in the system. There are some methodologies that are used for this aim. Minimizing many risks at the same time requires a multi objective solution methodology. A fuzzy based goal programming model is proposed to minimize the risk factors in a pharmaceutical supply chain in this paper. Linguistic expressions are used to define the importance of risks. To increase a deep and sensitive analysis, the fuzzy set theory is adopted in the proposed methodology that consists of fuzzy analytic hierarchy process (AHP) and goal programming (GP). Firstly a fuzzy ahp is used to prioritize the risks that can occur in pharmaceutical supply chain. The risks are related to demand planning, transport and storing conditions in pharmaceutical sector. Then a goal programming model is developed to minimize these risks. A real case application in pharmaceutical warehouse company in turkey is analyzed to check and confirm the model.
Keywords: Goal programming; the fuzzy set theory; AHP; pharmaceuticals; risk minimization; SUPPLY CHAIN; MANAGEMENT; MODEL; OPTIMIZATION; ISSUES; ENVIRONMENT; STRATEGIES; INDUSTRY; NETWORK; Computer Science; Science & Technology - Other Topics